Modern possibilities for using stem cells in diabetes mellitus - Ivan Ivanovich Dedov (Endocrinology Research Centre, 2014)
Diabetes mellitus (DM) is characterised by relative or absolute insulin deficiency. The currently available treatment methods for DM cannot provide normal blood glucose level without hypo- or hyperglycaemia episodes, thus failing to completely prevent the development of diabetic complications. Replacement of ?-cells (transplantation of the pancreas or ?-cells) is accompanied by complications and requires life-long immunosuppressive therapy that is not always followed by restoration of insulin independence; there is also a substantial deficit of donors. Stem cells do not cause such negative effects and can be used in therapy to avoid such problems. Allogeneic stem cell transplantation is complicated by immune rejection of a transplant, whereas the use of embryonic stem cells is associated with ethical concerns, complicated cell line selection, and risk of teratoma formation. The present review focuses on therapeutic pathways of autologous transplantation of tissue stem cells in order to restore the ?-cell pool, for immune reconstitution and modulation of the immune response in DM patients.